The Association of Self‐Reported Sleep, Weight Status, and Academic Performance in Fifth‐Grade Students. (18th January 2013) - Stroebele, Nanette; McNally, Janise; Plog, Amy; Siegfried, Scott; Hill, James O.
ABSTRACT BACKGROUND To improve support and justification for health promotion efforts in schools, it is helpful to understand how students' health behaviors affect academic performance. METHODS Fifth‐grade students completed an online school‐administered health survey with questions regarding their eating behavior, physical activity, academic performance, and sleep patterns. Differences in health behaviors were examined by sex, self‐reported weight status, and sufficient (≥9 hours) versus insufficient sleep. Logistic regression was used to determine the relationship between academic performance and the health behaviors. RESULTS One third of the sample did not get the recommended amount of physical activity and more than half of the students watched television ≥ 2 hours/day. Self‐reported overweight status was related to lower self‐reported academic performance, fewer lunch and breakfast occasions, less physical activity, not meeting the recommendations for vegetable and soda consumption as well as hours of television watching. Sufficient sleep (≥9 hours/night) was associated with better grades, meeting the recommended hours of daily television watching and video game playing, being more physically active and increased breakfast and lunch frequency. Percentage of serving free/reduced lunch, soda consumption, breakfast frequency, amount of physical activity, and television watching were associated with academic performance. CONCLUSION More positive health behaviors generally were associated with better academic performance. Promoting healthy behaviors in schools might improve not only students' health academic performance as well.